Impact of unit design on intensive care unit clinicians: a scoping review protocol. (December 2019) - Frechette, Julie; Frati, Francesca Y. E.; Octeau, Daphné; Bitzas, Vasiliki; Lavoie-Tremblay, Mélanie
ABSTRACT: Objective: This scoping review aims to identify the known impact of unit design on intensive care unit clinicians, and more specifically, to explore similarities and differences across critical care settings. Introduction: Construction and infrastructure renewal represent great opportunities for designing units that enhance patient care, as well as support the work of clinicians. A growing body of evidence is showing how unit design can impact clinical staff, but no reviews have been found that focus exclusively on clinicians within intensive care units. Inclusion criteria: The review will consider studies that include healthcare staff who offer direct patient care in adult or pediatric intensive care units. Studies that focus on the impact of design (related to physical environment features) on clinicians will be included. Methods: The proposed systematic review will be conducted in accordance with JBI methodology for scoping reviews. The search strategy aims to find published and unpublished studies. The databases to be searched will include Embase MEDLINE, PsycINFO, Healthstar and CINAHL. Retrieved studies will be assessed against the inclusion criteria by two independent reviewers. For the papers included in the scoping review, data will be extracted and quality assessed by two independent reviewers. The extracted data will be presented in tabular form, and a narrative summary will describe how the results relate to the review objective.